The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pharmaceutics15061572
|View full text |Cite
|
Sign up to set email alerts
|

Screening Libraries to Discover Molecular Design Principles for the Targeted Delivery of mRNA with One-Component Ionizable Amphiphilic Janus Dendrimers Derived from Plant Phenolic Acids

Abstract: Viral and synthetic vectors to deliver nucleic acids were key to the rapid development of extraordinarily efficient COVID-19 vaccines. The four-component lipid nanoparticles (LNPs), containing phospholipids, PEG-conjugated lipids, cholesterol, and ionizable lipids, co-assembled with mRNA via a microfluidic technology, are the leading nonviral delivery vector used by BioNTech/Pfizer and Moderna to access COVID-19 mRNA vaccines. LNPs exhibit a statistical distribution of their four components when delivering mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 282 publications
(604 reference statements)
0
6
0
Order By: Relevance
“…During the Covid-19 pandemic, our laboratory, together with the Weissman laboratory, developed and, starting in 2021, reported the first one-component IAJD systems that provided targeted delivery to spleen and lymph nodes, liver, and lung (Figures and ). A diversity of primary structures of IAJDs were discovered, and methodologies to target different organs via their hydrophilic parts were elaborated. The overall activity and the distribution to different organs was designed via the structure of their hydrophobic parts .…”
Section: Reprogramming the Living Factory In Vivo To Target The Deliv...mentioning
confidence: 99%
See 3 more Smart Citations
“…During the Covid-19 pandemic, our laboratory, together with the Weissman laboratory, developed and, starting in 2021, reported the first one-component IAJD systems that provided targeted delivery to spleen and lymph nodes, liver, and lung (Figures and ). A diversity of primary structures of IAJDs were discovered, and methodologies to target different organs via their hydrophilic parts were elaborated. The overall activity and the distribution to different organs was designed via the structure of their hydrophobic parts .…”
Section: Reprogramming the Living Factory In Vivo To Target The Deliv...mentioning
confidence: 99%
“…The overall activity and the distribution to different organs was designed via the structure of their hydrophobic parts. 232 Although IAJDs are in the early stage of development, their less complex synthesis, lower price, simple assembly and coassembly with mRNA, and increased stability compared with the four-component counterparts bring them to the forefront of targeted delivery platform methods to address current and future vaccines and therapeutics for cancer and degenerative and infectious diseases.…”
Section: Reprogramming the Living Factory In Vivo To Target The Deliv...mentioning
confidence: 99%
See 2 more Smart Citations
“…A methodology utilizing screening libraries was employed to discover the essential molecular design principles required for targeted mRNA delivery to organs and the facilitation of activity using a single-component ionizable multifunctional IAJD derived from plant phenolic acids. 35 These IAJDs co-assembled with mRNA, forming monodisperse DNPs with predictable dimensions through the straightforward process of injecting their ethanol solution into a buffer. The strategic placement of functional groups in the 1-component IAJDs demonstrated that hydrophilic regions determined the targeted organs, such as the liver, spleen, lymph nodes, and lungs, while the hydrophobic domain governed their activity.…”
Section: Nucleic Acid Deliverymentioning
confidence: 99%